Bridging the Gap between Single Nanoparticle Imaging and Global Electrochemical Response by Correlative Microscopy Assisted By Machine Vision (Small Methods 9/2022). Issue 9 (19th September 2022) - Godeffroy, Louis; Lemineur, Jean‐François; Shkirskiy, Viacheslav; Miranda Vieira, Mathias; Noël, Jean‐Marc; Kanoufi, Frédéric
Abstract : Back Cover In article number 2200659, Lemineur, Kanoufi, and co‐workers present a machine vision automatized analysis of the electrochemistry of a thousand individual nanoparticles from multi‐complementary operando optical and ex situ microscopies. Seeing the whole unveil electrocatalytic hydrogen evolution by Ni.